2013
DOI: 10.1088/1674-1137/37/1/016003
|View full text |Cite
|
Sign up to set email alerts
|

Method for improving the time resolution of a TOF system

Abstract: Method for improving the time resolution of a TOF system * LI Shao-Li( ) 1,2,3;1) HENG Yue-Kun( ) 1,2;2) ZHAO Tian-Chi( ) 4 FU Zai-Wei() 5 LIU Shu-Lin( ) 2 QIAN Sen( ) 2 LIU Shu-Dong() 2 CHEN Xiao-Hui( ) 1,2,3 JIA Ru( ) 6 HUANG Guo-Rui( ) 7 LEI Xiang-Cui( ) 1,2,3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Moreover, a combination of time-to-analog converter (TAC) with anolog-to-digital converter (ADC) currently has an advantage over time-to-digital converter (TDC) for signal digitization due to a better sampling resolution. Attempts [13,14] were also made by replacing the conventional electronics by waveform digitizers, which have the clear advantages in recording the full event signals but so far are still limited by their sampling rates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a combination of time-to-analog converter (TAC) with anolog-to-digital converter (ADC) currently has an advantage over time-to-digital converter (TDC) for signal digitization due to a better sampling resolution. Attempts [13,14] were also made by replacing the conventional electronics by waveform digitizers, which have the clear advantages in recording the full event signals but so far are still limited by their sampling rates.…”
Section: Introductionmentioning
confidence: 99%
“…The development of mountainous townships relies largely on the improvement of infrastructure conditions [5,6]. However, it is appreciated that the sustainability performance of infrastructure is poor in Chinese townships especially in mountainous regions [7]. Liu et al [8] suggested that mountainous townships usually have insufficient infrastructures, especially environmental infrastructure, and ineffective maintenance practice because of short-term behavior, which leads to typical problems such as short lifespan and serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar [1] pointed out that the construction regulations in mountainous regions should be made according to mountainous characteristics. The studies by other researchers investigate the effects of the geographic characteristics of mountainous regions on their economic development [2,7,10]. On the other hand, China's township serves as central places in rural China [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we evaluate its timing performance in a cosmic ray setup with plastic scintillators and fast PMTs. The timing performance is also compared with that of a Lecroy 10 GS/s oscilloscope [26] in a similar setup for evaluation of possibilities to improve timing performance of TOF systems [27].…”
Section: Introductionmentioning
confidence: 99%